(untitled) (Research, Society and Development, 2021)
In this manuscript, we aim to understand the conceptions of undergraduate students from Biological Sciences, Physical Education, Nursing, Nutrition and Public Health courses about the concept of “Living Being”. For this, interviews were conducted with these students, using the methodology of the Hermeneutic-Dialectical Circle (HDC). We also apply the Cloud Words to emphasize possible conceptual changes. It was observed that during the first stage, the majority of interviewees referred to this concept as "being that has life" concept that approaches the definition available in the dictionaries. However, due to the lack of a unified concept, it was necessary to apply a second stage, in which the interviewees had access to the answers of the other participants, in order to improve or re-signify their individual concepts. In the second stage, three participants did not change their answers after being in contact with the other interviewees’ concepts, while the others made some changes in their concept of a living being, however, the students’ answers still had divergences. In the third stage, students were brought together to propose a final consensus on the same issue, thus there was a positive reconstruction, in which the responses are showed cohesive and coincidentally aligned with several authors of the scientific literature. However, the CHD has proved to be an efficient tool for teaching-learning concepts, and it can be used to solve and build a consensus between groups and as an exercise in discussion on different topics.